(untitled) (Clinics, 2016)
OBJECTIVE: To analyze adherence to the recommended iron, zinc and multivitamin supplementation guidelines for preemies, the factors associated with this adherence, and the influence of adherence on the occurrence of anemia and iron, zinc and vitamin A deficiencies. METHODS: This prospective cohort study followed 58 preemies born in 2014 until they reached six months corrected age. The preemies were followed at a referral secondary health service and represented 63.7% of the preterm infants born that year. Outcomes of interest included high or low adherence to iron, zinc and multivitamin supplementation guidelines; prevalence of anemia; and prevalences of iron, zinc, and vitamin A deficiencies. The prevalence ratios were calculated by Poisson regression. RESULTS: Thirty-eight (65.5%) preemies presented high adherence to micronutrient supplementation guidelines. At six months of corrected age, no preemie had vitamin A deficiency. The prevalences of anemia, iron deficiency and zinc deficiency were higher in the low-adherence group but also concerning in the high-adherence group. Preemies with low adherence to micronutrient supplementation guidelines were 2.5 times more likely to develop anemia and 3.1 times more likely to develop zinc deficiency. Low maternal education level increased the likelihood of nonadherence to all three supplements by 2.2 times. CONCLUSIONS: Low maternal education level was independently associated with low adherence to iron, zinc and vitamin A supplementation guidelines in preemies, which impacted the prevalences of anemia and iron and zinc deficiencies at six months of corrected age.